Blunt Abdominal Trauma in Children: A Two Years Experience at Pediatric Surgery Centre in A Developing Country National Centre for Pediatric Surgery – Sudan From March 2014 – Feb 2016 - Alzain, Zulikha Ali Osman; Nugud, Fasial Abdel Galil (Gezira Journal of Health Sciences; Vol 15 No 1 (2019), 2019)
Background : Blunt abdominal trauma in pediatric is a common problem and is a cause of morbidity and mortality. The objectives of this work was to study blunt abdominal trauma, the most affected age group and gender, mode of trauma, common presentations most diagnostic tools, options of management and final outcome. Patients and Methods : This was retrospective and prospective descriptive hospital based study, conducted over 2 years (March 2014 – Feb 2016) in Gezira National Center for Pediatric Surgery. It was a total coverage sampling. including Fifty patients who were studied. Data was collected using a questionnaire (demographic data, age group, gender, residence, mode of trauma, time lapse between trauma and hospital arrival, common presentation, associated injury, diagnostic tools, initial management, the treatment option, duration of hospital stay and final outcome. Results : The most affected age group were 6 -10 years (52%), (11-15) years 22%; to less than 5 years 26%. Males 70% and females 30%. Mode of  trauma; RTA 32%, non-intentional 48%, intentional 20%). Time lapse between trauma and arrival (4-8 hours 36%, less than 4 hours 28%, 8-12 hours 8% more than 12 hours 28%. Presentation; abdominal pain, abdominal distention+ others 26%), (abdominal pain + abdominal distention 22%), (abdominal pain, abdominal distention+ pallor 14%), (abdominal pain + abdominal distention+ pallor + laceration 12%), (all mentioned 18%). Associated injuries (isolated abdominal injury 38%, chest trauma 34%, head trauma12%, lower limb 10%), The diagnostic tools; (Clinical diagnosis 40%, Clinical diagnosis and FAST scan 36%, Clinical diagnosis and others (x ray -CT) 24%). The treatment option, (Conservative 56 %, Surgical intervention 40%, Surgery after failure of conservation 4%). The intra-operative findings splenic injury 20%, small bowel injuries 8%. The duration of hospital stay, (1week 12%,1– 2 weeks 40%, more than 2 weeks 48%). Final outcome cured 78%, death 12%. Conclusion : Blunt abdominal trauma in pediatric is common problem(90%) and (10% penetrating) and is a cause of mortality (12%). It was mainly due to non- intentional trauma (48%). The most affected age group 6 -10 years (52%), males (70%) females (30%), no specific presentation, diagnosis by Clinical, FAST, CT, and others. Managed mainly conservative.